Composition of Renal Stone– An experience at Armed Forces Institute of Pathology - Naznin, Lubna; Saha, Debashish; Chowdhury, Md Jahangir; Akter, Yasmin; Sultana, Most Sarmin; Chowdhury, Ashif (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: In Asia the stone belt has been reported to stretch across our neighbouring countries Pakistan, India, Myanmar etc signifies a higher incidence of renal stone disease in Bangladesh. Objective: To determine the pattern of chemical composition of renal stones by semi-quantitative technique in patients presented to Armed Forces Institute of Pathology (AFIP) and to evaluate the predominant constituent present in them. Materials and Methods: This descriptive study was conducted at Armed Forces Institute of Pathology (AFIP), Chemical pathology department from October 2013 to October 2014. Renal stones of 37 Urolithiasis patients were analyzed chemically, using DiaSys analysis kit, employing titrimetric method for estimation of calcium and colorimetric method for Oxalate, Ammonium, Phosphate, Magnesium, Uric Acid and Cystine. Concentration of each individual component then was expressed in percentage and used to interpret renal stone composition using the calculation scale. Results: Males were more prone to renal stone disease, having male to female ratio 5.2:1. Urinary stones occur in all age groups, in this study age ranged from 4 to 72 years with mean age 38.8±16.0 years and mostly affected was the working age group 21 to 50 years (70.2%). Mixed components (i.e. mixed stone) rather than a single component was the commonest type constituting 83.8% of all renal stones. The commonest mixed stone found was Calcium Oxalate with Apatite (41.9 %). Pure Calcium Oxalate was the 2nd most common (10.8%) variant followed by Struvite stones (5.4%). Cystine and Brushite were the least common renal stones in this study. Conclusion: Calcium Oxalate was the most predominant chemical component in renal stones (94.6%). More research is needed to assess the frequency, types, and correlation of renal stones with environmental, dietary and genetic factors in Bangladesh. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 21-25